2017
DOI: 10.1063/1.4978909
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of the partial substitution of Ni by Cr on the transport, magnetic, and magnetocaloric properties of Ni50Mn37In13

Abstract: The structural, magnetic, and magnetotransport properties of Ni50-xCrxMn37In13 Heusler alloys have been synthesized and investigated by x-ray diffraction (XRD), field and pressure dependent magnetization, and electrical resistivity measurements. The partial substitution of Ni by Cr in Ni50Mn37In13 significantly improves the magnetocaloric effect in the vicinity of the martensitic transition (TM). This system also shows a large negative entropy change at the Curie temperature (TC), making it a candidate materia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 28 publications
1
1
0
Order By: Relevance
“…To summarize, replacing Ni by Cr and/or Co reduces e/a and T E drops to lower temperatures or vanishes completely, as is commonly expected. This is in full agreement to previous observations on Ni 50 Mn 37 In 13 where Cr on Ni reduces T M and, except for very small impurity concentrations, this substitution reduces the total entropy change at the structural transition temperature T M [69]. However, this holds only if we average over all possible isomers and orientations.…”
Section: Discussion and Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…To summarize, replacing Ni by Cr and/or Co reduces e/a and T E drops to lower temperatures or vanishes completely, as is commonly expected. This is in full agreement to previous observations on Ni 50 Mn 37 In 13 where Cr on Ni reduces T M and, except for very small impurity concentrations, this substitution reduces the total entropy change at the structural transition temperature T M [69]. However, this holds only if we average over all possible isomers and orientations.…”
Section: Discussion and Resultssupporting
confidence: 92%
“…Previous studies have shown that the excess Mn drives T M closer to room temperature and that complex magnetic martensitic phases such as 14 M can be avoided, see phase diagram in reference [66]. It has been further discussed in literature that Co tends to occupy Ni positions [31,67,68] whereas different Cr positions may be possible depending on processing conditions [44,69] The relevant magnetic structures are summarized in figure 1(d): the spins of Ni, Co, and Mn Y atoms are always aligned in parallel and define the FM background of the alloy while the Ga atoms are basically non-magnetic and can be neglected. Against this background, the magnetic alignment of Mn z and Cr define up to four (meta)-stable magnetic variants uu, ud, du, dd.…”
Section: Discussion and Resultsmentioning
confidence: 99%